Impact of COVID-19 pandemic on athletes with disabilities preparing for the Paralympic Games in Tokyo - Urbanski, P.; Szeliga, L.; Tasiemski, T. (BMC Research Notes, 2021)
Objective: The main aim of the study was to assess the impact of COVID-19 pandemic on athletes preparing for the Tokyo 2021 Paralympic Games during the lockdown period in Poland. The study involved 166 athletes, members of either the Polish Paralympic Committee or the Polish Sports Association for the Disabled `Start`, two organizations responsible for managing and regulating sports played by persons with disabilities in Poland. Results: Athletes with disabilities have been strongly affected by the pandemic and the resultant lockdown, which limited or prevented their participation in training sessions and possibly hampered their future sport performance during the Tokyo 2021.